Experimental evaluation of adobe mixtures reinforced with jute fibers. (22nd March 2021) - Araya-Letelier, G.; Antico, F.C.; Burbano-Garcia, C.; Concha-Riedel, J.; Norambuena-Contreras, J.; Concha, J.; Saavedra Flores, E.I.
Graphical abstract: Highlights: Varying dosages/lengths of Jute fibers (JFs) are incorporated in adobe mixtures (AMs). Negatively, high JF dosages increase the capillary water absorption of AMs. JFs do not affect the compressive and flexural strength of AMs. JFs improve the thermal/cracking control/toughness/water erosion performance of AMs. The combination of 2.0 wt%-15 mm JFs presents the best performance among AMs. Abstract: Due to their sustainability as well as physical and mechanical performance, different natural fibers, both vegetal and animal fibers, have been successfully used in adobe mixtures (AMs) to enhance properties such as cracking control, flexural toughness and water erosion resistance, among others. However, the use of jute fibers (JFs), one of the most largely produced vegetal fiber worldwide, has not been extensively studied on AMs. Consequently, this study evaluates the effects of the incorporation of varying dosages (0.5 and 2.0 wt%) and lengths (7, 15, and 30 mm) of JFs on the physical/thermal/mechanical/fracture and durability performance of AMs, a specific type of earth-based construction material widely used globally. Experimental results showed that the incorporation of 2.0 wt% dosages of JFs increased the capillary water absorption of AMs, which might affect AM durability. The latter result could be explained by the additional porosity generated by the spaces left between the JFs and the matrix of adobe, as well as the inherent water absorption of the JFs. The incorporation of JFs significantly improved the behavior of AMs in terms of thermal conductivity, drying shrinkage cracking control, flexural toughness and water erosion performance, without affecting their compressive and flexural strength. For example, flexural toughness indices were increased by 297% and crack density ratio as well as water erosion depth values were reduced by 93% and 62%, respectively, when 2.0 wt%-15 mm length JFs were incorporated into AM. Since the latter combination of JF dosage and length provided the overall best results among AMs, it is recommended by this study as JF-reinforcement scheme for AMs for construction applications such as adobe masonry and earth plasters.